2017
DOI: 10.21608/mjppf.2017.176024
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF KAOLIN APPLICATIONS ON FRUIT SUNBURN, YIELD AND FRUIT QUALITY OF BALADY MANDARIN (Citrus reticulata, Blanco)

Abstract: Sunburn is a major problem caused by high temperature and direct solar radiation, which leads to significant economic losses in Balady mandarin yield. So, a field experiment was conducted during 2014 and 2015 seasons at a private orchard situated in Motobus, Kafr El-Sheikh governorate, Egypt, to study the effect of foliar spray of 0, 2, 3 and 4% kaolin, twice or three times at May, June and July on sunburn percentage and fruit quality of Balady mandarin trees. The obtained results showed that, kaolin foliar ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Kerns and Wright [15] reported that kaolin application on lemon trees lowered the temperature of the fruit surface, reduced sun injuries, and improved yield and fruit quality. Ennab et al [18] mentioned that kaolin foliar spraying at concentrations of 3% and 4% decreased leaf heat and fruit surface temperature and reduced the number of sunburned fruits of 'Balady' mandarin trees. Baiea et al [3] found that kaolin foliar spray at concentrations of 25.5 and 75 g/L reduced fruit sunburn damage and improved the yield and fruit quality of Keitt mango fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Kerns and Wright [15] reported that kaolin application on lemon trees lowered the temperature of the fruit surface, reduced sun injuries, and improved yield and fruit quality. Ennab et al [18] mentioned that kaolin foliar spraying at concentrations of 3% and 4% decreased leaf heat and fruit surface temperature and reduced the number of sunburned fruits of 'Balady' mandarin trees. Baiea et al [3] found that kaolin foliar spray at concentrations of 25.5 and 75 g/L reduced fruit sunburn damage and improved the yield and fruit quality of Keitt mango fruits.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it reduces the adverse effects of drought stress. The effects of lowering temperature are reducing water consumption, increasing chlorophyll content, maintaining the quantitative and qualitative characteristics of the product, and preventing bursting and sunburn of citrus fruit, which was found in research conducted on Balady mandarin (Citrus reticulata Blanco) [29] and grapefruit [28] have been evident. Figure 6 shows page mandarin (C. reticulata) trees sprayed with kaolin.…”
Section: Green and Reticular Polyethylene Shades With One (A) Two (B)...mentioning
confidence: 93%
“…Another strategy proposed in recent years to deal with the harmful effects of drought stress and the high summer temperature is using antiperspirant and sunlightreflective compounds, such as kaolin. Kaolin is a natural clay with an aluminum phyllosilicate (Al 2 Si 2 O 5 (OH) 4 ) structure, which is chemically neutral in a wide range of pH changes and does not harm living organisms [28,29].…”
Section: Drought Stress and Its Management And Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sunburned satsuma mandarin fruits are undesirable among farmers and consumers. Although previous citrus studies to suppress sunburn using kaolin, calcium carbonate, and shading treatment have been conducted [ 18 , 19 , 20 ], few systematic studies showed the effect of sunburn on anatomical difference and physiological responses to satsuma mandarin quality.…”
Section: Introductionmentioning
confidence: 99%